2019
DOI: 10.2169/internalmedicine.1907-18
|View full text |Cite
|
Sign up to set email alerts
|

An Autopsy Case of Bing-Neel Syndrome: Discrepancy between the Radiological and Pathological Findings

Abstract: A 64-year-old man previously diagnosed with Waldenstrom's macroglobulinemia presented to our hospital with confusion. Magnetic resonance imaging (MRI) revealed diffuse meningeal enhancement. The patient was diagnosed with Bing-Neel syndrome (BNS) based on an elevated IgM index and the presence of monoclonal IgM protein, as detected by immunofixation electrophoresis of the cerebrospinal fluid. The patient underwent intrathecal and systemic chemotherapy but ultimately died of pneumonia. An autopsy revealed exten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Dural and parenchymal involvement were present in 37.5% and 41.7% of patients, respectively. Autopsy results have observed more extensive meningeal and perivascular infiltration by malignant cells than that revealed by MRI 5 . the gold standard for diagnosis is a histological biopsy of the affected area or CSF analysis by flow cytometry demonstrating malignant cells as previously outlined 1 …”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Dural and parenchymal involvement were present in 37.5% and 41.7% of patients, respectively. Autopsy results have observed more extensive meningeal and perivascular infiltration by malignant cells than that revealed by MRI 5 . the gold standard for diagnosis is a histological biopsy of the affected area or CSF analysis by flow cytometry demonstrating malignant cells as previously outlined 1 …”
Section: Discussionmentioning
confidence: 95%
“…Autopsy results have observed more extensive meningeal and perivascular infiltration by malignant cells than that revealed by MRI. 5 the gold standard for diagnosis is a histological biopsy of the affected area or CSF analysis by flow cytometry demonstrating malignant cells as previously outlined. 1 There is no established treatment regimen for BNS to date.…”
Section: Discussionmentioning
confidence: 99%
“…Autopsy reports are scarce given the rarity of this disease, but there appears to be prominent perivascular infiltration by malignant cells without deposition of IgM in BNS that is not readily apparent on MRI imaging. 10 Despite these sensitive imaging techniques, MRI cannot distinguish between other forms of CNS lymphoma thus necessitating further testing with both CSF analysis and tissue biopsy. CSF should be collected and sent for cytology, flow cytometry, in addition to electrophoresis and immunofixation in order to determine whether M-protein and specific immunoglobulin elevations are present within the CNS.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports present similar diagnostic challenges due to the discrepancy between the diverse clinical presentation of the disease and scarce or missing MRI findings. Interestingly, an autopsy case report concluded that the pathological involvement of CNS can be even more extensive than the MRI suggested [17]. Thus when even minor neurologic symptoms occur in a patient with known WM history, extensive examinations should be initiated to exclude BNS.…”
Section: Discussionmentioning
confidence: 99%